THE INFLUENCE OF WORK CULTURE AND WORK ENVIRONMENT ON EMPLOYEE WORK EFFECTIVENESS AT THE MINISTRY OF POPULATION AND FAMILY DEVELOPMENT / BKKBN REPRESENTATIVE OF SOUTH SULAWESI PROVINCE - Wahyu Veriadi Ramadhan; Anwar Anwar; Rezky Amalia Hamka (Universitas Negeri Makassar, 2026)
Abstract: This study aims to analyze the influence of work culture and work environment on employee work effectiveness at the Ministry of Population and Family Development (BKKBN) Representative Office of South Sulawesi Province. This study uses a quantitative approach with a survey method. Data were collected through questionnaires distributed to 67 employees with a purposive sampling technique. Data analysis used multiple linear regression with the help of SPSS Statistics 27. The results of the study indicate that work culture has a positive and significant effect on employee work effectiveness, work environment has a positive and significant effect on employee work effectiveness, and work culture and work environment simultaneously have a positive and significant effect on employee work effectiveness. These findings indicate that improving a good work culture and a conducive work environment can improve employee work effectiveness in achieving organizational goals.Keywords: Work culture, work environment, work effectiveness